Safety, Collaboration, and Empowerment: Trauma-Informed Archival Practice - Wright, Kirsten; Laurent, Nicola (Archivaria)

(untitled) (Association of Canadian Archivists, 2021)
In order to undertake liberatory memory work, engage effectively with communities and individuals, and centre people rather than records in their work, archival organizations must be aware of trauma and its effects. This article introduces the concept of trauma-informed practice to archives and other memory organizations. Trauma-informed practice is a strengths-based approach for organizations that acknowledges the pervasiveness of trauma and the risk and potential for people to be retraumatized through engagement with organizations such as archives and seeks to minimize triggers and negative interactions. It provides a framework of safety and offers a model of collaboration and empowerment that recognizes and centres the expertise of the individuals and communities documented within the records held in archives. Traumainformed practice also provides a way for archivists to practically implement many of the ideas discussed in the literature, including liberatory memory work, radical empathy, and participatory co-design. This article proposes several areas where a trauma-informed approach may be useful in archives and may lead to trauma-informed archival practice that provides better outcomes for all: users, staff, and memory organizations in general. Applying trauma-informed archival practice is multidimensional. It requires the comprehensive review of archival practice, theory, and processes and the consideration of the specific needs of individual memory organizations and the people who interact with them. Each organization should implement trauma-informed practice in the way that will achieve outcomes appropriate for its own context. These out comes can include recognizing and acknowledging past wrongs, ensuring safety for archives users and staff, empowering communities documented in archives, and using archives for justice and healing.